2014
DOI: 10.1007/7854_2014_322
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Correlates of Positive Symptoms in Schizophrenia

Abstract: Patients with schizophrenia have been hypothesized to have a functional impairment in filtering irrelevant sensory information, which may result in positive symptoms such as hallucinations or delusions. Many evidences suggest that abnormalities in the event-related brain potentials (ERPs), resting state electroencephalography (EEG) and synchronized oscillatory activity of neurons may reflect core pathophysiological mechanisms of schizophrenia. Abnormalities in amplitude and latency of the ERPs reflecting aberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 100 publications
4
9
0
Order By: Relevance
“…The results of the correlation analysis in the present study revealed that the PSE of delay detection was correlated with the PSE of agency attenuation, indicating that sensorimotor integration ability was closely related to the explicit SoA. A previous study also reported that patients with schizophrenia exhibiting an abnormal explicit SoA simultaneously exhibited impaired sensorimotor integration [29], suggesting a close relationship between sensorimotor integration ability and explicit SoA from a clinical perspective. To the best of our knowledge, the current study is the first to successfully reveal the relationship between sensorimotor integration and SoA with an experimental paradigm involving the delay detection task and the agency attribution task.…”
Section: Discussionsupporting
confidence: 66%
“…The results of the correlation analysis in the present study revealed that the PSE of delay detection was correlated with the PSE of agency attenuation, indicating that sensorimotor integration ability was closely related to the explicit SoA. A previous study also reported that patients with schizophrenia exhibiting an abnormal explicit SoA simultaneously exhibited impaired sensorimotor integration [29], suggesting a close relationship between sensorimotor integration ability and explicit SoA from a clinical perspective. To the best of our knowledge, the current study is the first to successfully reveal the relationship between sensorimotor integration and SoA with an experimental paradigm involving the delay detection task and the agency attribution task.…”
Section: Discussionsupporting
confidence: 66%
“…While no between-group differences were observed for intensity MMN amplitude, in EP participants we observed that increased positive symptoms are associated with increased intensity MMN peak latency. This offers some small support to the theory that the aberrant intrinsic organization of functional brain networks associated with positive symptoms can be indexed with electrophysiological measures 68 and suggests that this may extend to the early phase of the illness. While this is, to our knowledge, the first report of an association between MMN latency and clinical symptoms in early phase schizophrenia, similar findings of increased positive symptoms being observed with concurrent decreases in MMN amplitude have been seen in chronic schizophrenia, albeit with duration 69 and novel 53 deviants.…”
Section: Mmn Amplitudes and Latenciesmentioning
confidence: 60%
“…A vast EEG literature has documented different abnormalities of neuronal activity in subjects with chronic SCZ, as compared to healthy controls (HCs) ( 29 , 33 , 43 – 49 ). In particular, several studies have consistently reported alterations in the activity of the whole spectrum of frequency bands ( 49 – 53 ), changes in MSs topography and/or other parameters ( 46 , 47 , 54 ) and a reduction of amplitude in ERPs, such as N100 ( 55 – 58 ), mismatch negativity (MMN) ( 59 , 60 ), and P300 ( 33 , 57 , 61 ). Furthermore, these alterations have been related to the severity of symptoms, as well as cognitive and functional impairment in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%